DETERMINATION OF OPTIMAL COMPOSITION OF GASEOUS ACID FOR TREATMENT BOTTOMHOLE ZONE - Возний, Василь Романович; Вольченко, Дмитро Олександрович; Лагуш, Роман Федорович; Катрич, Василь Дмитрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The state of the bottomhole formation zone has a determining effect on the productivity of the open horizons. Deterioration of reservoir filtration and capacitance in the bottomhole zone of oil, gas and injection wells leads to a decrease in their productivity. The use of gaseous acids and their mixtures with liquids makes it possible to create new technologies, improve and intensify known methods. The high efficiency of new and improved technologies using nitrogen and natural gas is due to its physico-chemical properties and the influence on hydrodynamic conditions of filtration processes. The optimal composition of the aerated acid solution for treating the bottomhole formation zone is scientifically based.